FINDING THE DOMINATING AMINO ACIDS IN DENGUE VIRUS (TYPE-1) STUDY ON MINING FREQUENT ITEMSETS - D.KERANA HANIREX; DR.K.P.KALIYAMURTHIE (International Journal of Pharma and Bio Sciences, 2013)
Research on biological science is one of the emerging task. One approach is finding the hidden patterns and association rules over the patterns. This proposed system finds the most dominating amino acids in dengue virus type-1 (DEN-1) . There are no specific vaccines and drugs are predicted for dengue virus yet. This system finds the dominating amino acids among the infected protein sequences which causes infections in human. The dominating amino acids have been identified using Apriori Algorithm in data mining. We found that association rule reveals the association between the protein and protein sequence. This is a novel attempt which finds the most informative association rules using Apriori algorithm implemented through Java. The generated information can be useful to the drug designers. Our findings reveals that Leucine(L), Phenylalanine (F),Lysine(K),Serine(S) and Glycine(G) are the dominating amino acids in Dengue Virus Type-1.Hence this system can be a potential candidates for the drug designers to develop the antibiotics for the dengue fever.